2016
DOI: 10.1016/j.ecoleng.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Metal removal mechanisms in a short hydraulic residence time subsurface flow compost wetland for mine drainage treatment

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International licence Newcastle University ePrints -eprint.ncl.ac.uk Gandy CJ, Davis JE, Orme PHA, Potter HAB, Jarvis AP. Metal removal mechanisms in a short hydraulic residence time subsurface flow compost wetland for mine drainage treatment. Ecological Engineering 2016, 97, 179-185.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 33 publications
1
32
1
1
Order By: Relevance
“…Details of the pilot scale treatment system at Rampgill were reported by Gandy et al (2016) and are summarized here. The Rampgill Mine was exploited for Pb and Zn, mine water discharge from the abandoned mine is at pH 7.7 and contained Zn (2.2 mg L −1 ) and sulfate (134 mg L −1 ).…”
Section: Pilot Study Of Mine Water Bioremediation At Rampgill Ukmentioning
confidence: 99%
“…Details of the pilot scale treatment system at Rampgill were reported by Gandy et al (2016) and are summarized here. The Rampgill Mine was exploited for Pb and Zn, mine water discharge from the abandoned mine is at pH 7.7 and contained Zn (2.2 mg L −1 ) and sulfate (134 mg L −1 ).…”
Section: Pilot Study Of Mine Water Bioremediation At Rampgill Ukmentioning
confidence: 99%
“…Processes of metal removal and mobilisation in a wetland include sedimentation, adsorption, complexation, bio‐remediation, uptake by plants and microbially mediated reactions including oxidation and reduction (Perry & Kleinmann ; Dunbabin & Bowmer ; Whitehead & Prior ; Akcil & Koldas ; Stoltz & Greger, ; Sheoran & Sheoran ; Nyquist & Greger ; Gandy et al . ). Several studies have also reported significant water quality improvements in terms of metal removal by wetland substrate (Garcia et al .…”
Section: Introductionmentioning
confidence: 97%
“…The effective retention of mine effluent by wetland substrate has been documented in different mining areas in the world (Faulkner & Richardson 1989;Dunbabin & Bowmer 1992;Johnson & Hallberg 2005). Processes of metal removal and mobilisation in a wetland include sedimentation, adsorption, complexation, bio-remediation, uptake by plants and microbially mediated reactions including oxidation and reduction (Perry & Kleinmann 1991;Dunbabin & Bowmer 1992;Whitehead & Prior 2005;Akcil & Koldas 2006;Stoltz & Greger, 2006;Sheoran & Sheoran 2006;Nyquist & Greger 2009;Gandy et al 2016). Several studies have also reported significant water quality improvements in terms of metal removal by wetland substrate (Garcia et al 2001;Nyquist & Greger 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these have circum-neutral pH and, in contrast to extremely acidic mine waters, contain relatively little soluble iron, though concentrations of other transition metals, such as zinc, lead, and cadmium can exceed water quality guidelines. Various treatments options have been suggested and trialed for remediating mine water of this kind, including constructed wetlands and compost bioreactors which use microbiological processes, in tandem with chemical adsorption, to remove potentially toxic metals (Younger et al, 2003;Gandy et al, 2016). A primary role of microorganisms in this context is to generate hydrogen sulfide from the dissimilatory reduction of more oxidized forms of sulfur (such as sulfate), which in turn reacts with many metals that commonly occur in mine discharge waters to form insoluble sulfide phases (Johnson and Hallberg, 2005).…”
Section: Introductionmentioning
confidence: 99%